THE ROLE OF BRAND IMAGE IN MEDIATING THE EFFECT OF ELECTRONIC WORD OF MOUTH (EWOM) ON MIXUE PRODUCT PURCHASE DECISIONS IN DENPASAR CITY - Alvin Richard Christian Okhotan; I Gde Ketut Warmika (Adisam Publisher, 2025)
This study aims to examine the effect of Electronic Word of Mouth (EWOM) on Purchase Decisions with Brand Image as a mediating variable for Mixue products. The research was conducted in Denpasar City using data collection through questionnaires with a sample of 100 respondents who had purchased and consumed Mixue products. The data analysis techniques employed were Descriptive Statistics and Inferential Statistics. The results of the analysis indicate that EWOM has a positive and significant effect on Brand Image and Purchase Decisions, Brand Image has a positive and significant effect on Purchase Decisions, and serves as a mediator in influencing the effect of EWOM on Purchase Decisions. Theoretically, these findings reinforce consumer behavior literature by confirming that EWOM can affect purchase decisions both directly and indirectly through brand image. Practically, this study provides insights for Mixue to optimize digital marketing strategies by strengthening brand image, enhancing customer experience, and leveraging positive EWOM through reviews, social media interactions, and collaborations with influencers.